2019
DOI: 10.2478/johr-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Plastic Cover on the Protection of Sweet Cherry Fruit Against Cracking, on the Microclimate under Cover and Fruit Quality

Abstract: To study possibility of protection of sweet cherry fruit against cracking several rows of ‘Lapins’ sweet cherry (Prunus avium L.) trees grafted on ‘Colt’ rootstock, spaced 5 × 2.5 m and trained to a central leader were covered with a plastic foil to a height of 5 m. Several rows were left uncovered as a control. In the years 2016 and 2018, sun irradiation, air temperature and fruit quality were evaluated. The plastic cover reduced solar irradiation under the tunnel roof by around 40%. Light distribution within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Deployment of the www.nature.com/scientificreports/ rain covers in early November resulted in consistently warmer temperatures, reduced light levels, and greatly reduced wind speeds relative to the netted PCS block. These are intuitive findings that are consistent with other reports [35][36][37][38][39] although the differences were relatively minor in light and temperature and this is the first report of the effects on wind under rain covers to the best of our knowledge. In contrast, average and minimum RH, VPD and ETo were similar, although it is notable that average maximum VPD was only markedly lower under the covered PCS in December and only noticeably higher in February.…”
Section: Discussionsupporting
confidence: 93%
“…Deployment of the www.nature.com/scientificreports/ rain covers in early November resulted in consistently warmer temperatures, reduced light levels, and greatly reduced wind speeds relative to the netted PCS block. These are intuitive findings that are consistent with other reports [35][36][37][38][39] although the differences were relatively minor in light and temperature and this is the first report of the effects on wind under rain covers to the best of our knowledge. In contrast, average and minimum RH, VPD and ETo were similar, although it is notable that average maximum VPD was only markedly lower under the covered PCS in December and only noticeably higher in February.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, there have been no formal reports that accurately define the effects of microclimate conditions under high tunnels on sweet cherry fruit quality, fruit mineral composition, and storage potential, particularly under Mediterranean conditions. However, a few reports have dealt with high tunnel cherry cultivation under continental and oceanic climates, such as in Michigan (USA), Norway, and Poland [10,11,28]. In an earlier report we found that sweet cherry fruit under high tunnels in Chile's Central Valley were larger and less firm than fruit grown out in the open, but their postharvest storage potential, mineral composition, and incidence of physiological disorders were not assessed [26].…”
Section: Introductionmentioning
confidence: 93%
“…The main obstacle in cherry production is fruit cracking induced by rain. This condition defect causes severe losses in many production areas of sweet cherry [19,86,87]. Cracking is frequently the result of a wet fruit surface prior to harvest; therefore, water uptake through the skin and pedicel results in fruits provoking an increase in turgor, inducing cracking [88,89].…”
Section: Discussionmentioning
confidence: 99%